Modular Production Networks in Electronics: The Nexus between Management and Economics Research - Gangnes, Byron (Institutional Knowledge at Singapore Management University, 2004)
In the last two decades, the electronics industry has evolved from a vertically integrated industry to a vertically segmented one. This transformation has often been attributed to the modularization of electronic products. In this paper, we argue that the degree of modularity is an active choice variable for a firm. As a result, it is necessary to focus on the underlying factors that drive both modularity and the organization of production. This provides insights into the transformation taking place in global electronics production, with vertical fragmentation, horizontal consolidation, and the growth of Asian electronics production.